Nucleotide-dependent activities of FtsA regulate the early establishment of a functional divisome during the Escherichia coli cell cycle - Morrison, Josiah J.; Ferreira, Colby N.; Siler, Evelyn M.; Nelson, Katie; Trebino, Catherine E.; Piraino, Benjamin; Camberg, Jodi L. (Frontiers in Microbiology, 2023)
During cell division in Escherichia coli, the highly conserved tubulin homolog FtsZ polymerizes and assembles into a ring-like structure, called the Z-ring, at the site of septation. For recruitment to the membrane surface, FtsZ polymers directly interact with membrane-associated proteins, predominantly FtsA in E. coli. FtsA shares structural homology with actin and, like actin, hydrolyzes ATP. Yeast actin detects nucleotide occupancy through a sensor region adjacent to the nucleotide binding site and adopts distinct conformations in monomeric and filamentous actin. Bacterial actin homologs also display considerable conformational flexibility across different nucleotide-bound states and polymerize. Here, we show that several amino acid residues proximal to the nucleotide binding site in FtsA are critical for function in vitro and in vivo. Each of these residues are important for ATP hydrolysis, phospholipid (PL) binding, ATP-dependent vesicle remodeling, and recruitment to the divisome in vivo, to varying degrees. Notably, we observed that Ser 84 and Glu 14 are essential for ATP-dependent vesicle remodeling and magnesium-dependent membrane release of FtsA from vesicles in vitro, and these defects likely underlie the loss of function by FtsA(E14R) and FtsA(S84L) in vivo. Finally, we demonstrate that FtsA(A188V), which is associated with temperature-sensitive growth in vivo, is defective for rapid ATP hydrolysis and ATP-dependent remodeling of PL vesicles in vitro. Together, our results show that loss of nucleotide-dependent activities by FtsA, such as ATP hydrolysis, membrane binding and release, and, most importantly, ATP-dependent PL remodeling, lead to failed Z-ring assembly and division defects in cells.